De volta ao passado: Revisitando a história biogeográfica das florestas neotropicais úmidas - Sobral-Souza, Thadeu [UNESP]; Lima-Ribeiro, Matheus Souza (Oecologia Australis, 2017)
The high biological diversity observed in the tropical rainforests is a fact that intrigues researchers around the world, especially regarding historical processes responsible for their origin and maintenance. For Neotropical rainforests is not different. Here, we revisited the main hypotheses about the origins and changes in Neotropical rainforests over time, based on different studies as paleoclimatic, fossil pollen, phylogeographic, ecological models and evolution, in order to synthesize its biogeographical history and advancing in debate about its connections and preterit fragmentations. Evidence suggests that there is no single cause shaping the biodiversity of these environments. In reality, the complexity seems to be the rule in this region, inferred by several hypotheses and many particularities for each studied taxonomic group.
Back to the past: Revisiting the biogeographic history of neotropical rainforests
Keywords: Amazon; Atlantic forest; Biodiversity; Biogeography; Neotropic